Integrated Tamil News Storage and Analysis Using Big Data Analytics - Anandakumar, B; Manimegalai, R (International Journal of Computer Sciences and Engineering, 2025)
This is a Application of Big data analytic. In this concept all Tamil news are stored into Big data analytical tools such as R Tool, MangoDB, Hadoop etc. The News is stored in the form of text, Photos, videos, audio etc. The News is gathered from all daily Tamil news paper, Epaper, Ebook and Social Media Content. Then this News will be analysed in various Angle. Moreover Government Policies, Plan, Advertisement etc. will be stored into the big data Tool. This information is stored into Date wise, month wise and year wise. The news will be classified into various types such as political, Sports, International, national, Local news etc. This is stored into the current details as well as past details. So, we can analysis the every news which is arising in the current problem. Now days Social Networks impact all areas of society. So, the Social Media information’s are stored into big data tools. The news is collected over 100 years. So, all the information’s are digitized. This proposed project is stored information’s of Old literatures of Tamil. Moreover the proposed project stored information’s of archaeological information like stone inscription, Palm leaf etc. So, this project consists of all details of Tamil. So, we can store and analyse information’s. Moreover it will be stored into Cloud Computing Environment. So, we can access anywhere else. The proposed project is stored all type of Tamil news come from various sources. Now days all the daily are converted into pdf format. So, that will be stored into Big Data Tool. The Proposed Project Consist of old literature of Tamil, Tamil Stone Age arts, palm leaf letters etc.